The Effect of the Competency of the Application, Regulatory Completeness and Implementation of the Siskeudes Application on Effectiveness Gampong Budget Management (Study in Gampong-Gampong in the District of Sigli City, Pidie Regency) - Ahmad Husnizal; Ridwan Ibrahim; Syukriy Abdullah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aim of this research is to examine the influence of state apparatus competency, completeness of regulations and the implementation of SISKEUDES application both as simultaneous and separately on the effectiveness of village fund management in sub-districs of Sigli city, district of Pidie. The research population were all villages in sub-district of Sigli city, District of Pidie, which were 15 villages in total, with research respondents including; Village headman, Village secretary, Treasurer, Head of General Affairs and Head of Development Affairs. The source of data used primary data which was questionnaires results of respondents. The data collection technique was conducted by the documentation. The analytical method was Multiple Linear Regression Analysis. The results showed that both simultaneous and separatedly, Competence apparatus, the completeness of regulations and the implementation of the SISKEUDES application together have a positive effect on the effectiveness of village budget management. Competence apparatus has a positive effect on the effectiveness of village budget management. Completeness of regulations has a positive effect on the effectiveness of village budget management. The application of the SISKEUDES application has a positive effect on the effectiveness of village budget management.